Real-time data acquisition system for the Identification of dynamic temperature models in a hydroponic greenhouse - Ferreira, P. M. (2013)
A real-time data acquisition and identification system implemented in a soil-less greenhouse located in the south of Portugal is described. The system performs real-time data acquisition from a set of sensors connected to a data logger.